Tumor Metastasis 2016
DOI: 10.5772/64812
|View full text |Cite
|
Sign up to set email alerts
|

The Selection Strategy for Circulating Tumor Cells (CTCs) Isolation and Enumeration: Technical Features, Methods, and Clinical Applications

Abstract: The key aim of the proposed chapter is to provide readers a brief description for the most important parts of the field of circulating tumor cells (CTCs): the core techniques, including negative and positive selection-based CTC isolation, and the differences between them. Most importantly, we will also review the clinical applications and important findings in clinical trials. The evidence-based review will not only help clinicians use CTCs to predict recurrence and foresee the disease-related outcomes but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 282 publications
(338 reference statements)
0
5
0
Order By: Relevance
“…The methodology we used, compared to the only FDA‐approved device, Cellsearch, showed a similar recovery rate and a better detection rate in late‐stage cancer settings . Most importantly, CTC testing based on the negative selection strategy has more chances to save cells with no CKs or EpCAM expressions . Those cells are possibly undergoing epithelial‐mesenchymal transformation, pushing cancer to grow, evolve, and probably leading to poor outcomes in patients with cancer.…”
Section: Discussionmentioning
confidence: 94%
“…The methodology we used, compared to the only FDA‐approved device, Cellsearch, showed a similar recovery rate and a better detection rate in late‐stage cancer settings . Most importantly, CTC testing based on the negative selection strategy has more chances to save cells with no CKs or EpCAM expressions . Those cells are possibly undergoing epithelial‐mesenchymal transformation, pushing cancer to grow, evolve, and probably leading to poor outcomes in patients with cancer.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, two large-scale meta-analysis studies, which included 3094 patients in the first study and 1329 patients in the second study, showed that the detection of CTCs correlated with a poor prognosis for CRC patients. 26 , 27 In addition, the optimal cut-off value of the number of CTCs for the prognostic value in patients positive for CTCs was undetermined 28 . Furthermore, only approximately one-third of the patients had detectable CTCs, and the discrimination of survival differences among those patients who were negative for CTCs was impossible.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the immunoaffinity assay is expensive, labor-intensive, and subject to large variability in the recovery rate (9-90%) mainly due to the variability in expression of surface markers [13,72]. Therefore, negative selection methods are developed to avoid some of the major disadvantages of the positive selection method, such as losing non-EpCAM CTCs and a relatively poor recovery rate [79]. In this approach, red blood cells are lysed followed by a CD45 (a common antigen of leukocytes) immuno-depletion process to remove leukocytes.…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
“…Therefore, all CTCs, either epithelial marker positive or negative, can be fully recovered, which makes the number of isolated CTCs larger than those by the positive method [75]. However, the background cells in negatively isolated samples are often mixed with numerous white blood cells and red blood cells, and hence, prohibit the downstream molecular analysis [79]. Therefore, more efficient and reliable methods are required for CTCs isolation.…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%